2017
DOI: 10.1002/clc.22772
|View full text |Cite
|
Sign up to set email alerts
|

Home monitoring after ambulatory implanted primary cardiac implantable electronic devices: The home ambulance pilot study

Abstract: Background The Home Monitoring (HM) system of cardiac implantable electronic devices (CIEDs) permits early detection of arrhythmias or device system failures. The aim of this pilot study was to examine how the safety and efficacy of the HM system in patients after ambulatory implanted primary CIEDs compare to patients with a standard procedure and hospitalization. Hypothesis We hypothesized that HM and their modifications would be a useful extension of the present concepts for ambulatory implanted CIEDs. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 19 publications
2
28
0
2
Order By: Relevance
“…The studies in English were geographically clustered, with 26 studies conducted in North America, among which 20 occurred in the United States [ 20 - 23 , 25 - 28 , 30 , 31 , 33 , 34 , 37 , 38 , 42 , 61 , 62 , 64 , 67 , 68 ] and 6 in Canada [ 29 , 40 , 49 , 51 , 63 , 66 ]. Among the 22 studies conducted in Europe, they were spread across countries, with 5 studies conducted in England and the United Kingdom [ 24 , 41 , 43 , 44 , 53 ]; 3 each in Denmark [ 50 , 52 , 58 ], Italy [ 32 , 45 , 55 ], the Netherlands [ 35 , 39 , 72 ]; 2 each in Austria [ 46 , 60 ] and Germany [ 47 , 54 ]; and 1 each in France [ 59 ], Spain (although not explicitly stated in the paper) [ 57 ], Norway [ 70 ], and Sweden [ 69 ]. Finally, 4 studies took place in Australia [ 36 , 56 , 71 , 73 ] and 3 in Asia, among which 2 were in Japan [ 13 , 65 ] and 1 in Taiwan [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies in English were geographically clustered, with 26 studies conducted in North America, among which 20 occurred in the United States [ 20 - 23 , 25 - 28 , 30 , 31 , 33 , 34 , 37 , 38 , 42 , 61 , 62 , 64 , 67 , 68 ] and 6 in Canada [ 29 , 40 , 49 , 51 , 63 , 66 ]. Among the 22 studies conducted in Europe, they were spread across countries, with 5 studies conducted in England and the United Kingdom [ 24 , 41 , 43 , 44 , 53 ]; 3 each in Denmark [ 50 , 52 , 58 ], Italy [ 32 , 45 , 55 ], the Netherlands [ 35 , 39 , 72 ]; 2 each in Austria [ 46 , 60 ] and Germany [ 47 , 54 ]; and 1 each in France [ 59 ], Spain (although not explicitly stated in the paper) [ 57 ], Norway [ 70 ], and Sweden [ 69 ]. Finally, 4 studies took place in Australia [ 36 , 56 , 71 , 73 ] and 3 in Asia, among which 2 were in Japan [ 13 , 65 ] and 1 in Taiwan [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 18 studies reported CEAs [ 24 , 25 , 27 , 34 , 35 , 39 - 41 , 44 , 46 , 50 , 53 , 54 , 59 , 60 , 70 , 71 , 73 ], 2 studies combined CEAs with clinical or budget impact analyses [ 48 , 62 ], 2 studies reported CUAs [ 36 , 52 ], and 1 study reported a CBA [ 13 ]; 8 studies denoted the evaluation as cost analysis [ 26 , 45 , 61 , 63 , 67 - 69 , 72 ], the term cost minimization was used in 4 studies [ 29 , 49 , 51 , 65 ], and 1 study reported relying on cost consequence analysis [ 43 ]. The remaining 17 studies stated that they evaluated a range of cost and outcome measures [ 21 , 23 , 28 , 30 - 33 , 37 , 38 , 42 , 47 , 55 - 58 , 64 , 66 ], and 2 studies relied on case studies to outline benefits, saving, expenditures, and outcomes [ 20 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations